AN ANALYSIS OF JARGON IN THE MOBILE LEGEND ONLINE GAMES - Novrianti, Febby Okta; Lestari, Noni Dwinka; Mahdiansyah, Viki; Sembiring, Lina Tri Astuty (Universitas Suryakancana, 2023)
Sociolinguistics and language are closely related. Sociolinguistics studies speakers and listeners of languages by studying various aspects. In this attachment between social and language, the application taken is sociolinguistics in jargon. Jargon is a special term used in a certain scope. Based on this research, it is known that researchers found various types of jargon. Jargon is not only special words that exist within the scope of society, but is also found in online games. In this study, the Mobile Legend Online Game is the object of analysis chosen by the researcher. Data collection and completion of analysis using a qualitative descriptive research type. The output of this study is a sociolinguistic analysis of the meaning of jargon in the Mobile Legend Online Game, using data reduction techniques, data display, and conclusion verification. The data taken is also based on terms that are often used by users of this game to communicate with fellow teams. Researchers have found 16 jargons that have denotative meanings and 10 jargons that have connotative meanings in the Mobile Legend Online Game. With the results of this study, the researcher hopes that this research can become significant data for the linguistic community and can also be a source of data, data benchmarks, and comparisons for future researchers, especially research on sociolinguistics. Based on this research, it is hoped that the results can add insight to readers about the meaning of jargon in various game situations and how it is used in conversations among users of the Mobile Legend Online Game.